2014
DOI: 10.1007/s10530-014-0806-y
|View full text |Cite
|
Sign up to set email alerts
|

Enemy release and genetic founder effects in invasive killer shrimp populations of Great Britain

Abstract: Arundell, K., Dunn, A., Alexander, J. L., Shearman, R., Archer, N., Ironside, J. (2015). Enemy release and genetic founder effects in invasive killer shrimp populations of Great Britain. Biological Invasions, 17 (5), 1439-1451. Document embargo until 04/11/2015The predatory ?killer shrimp? Dikerogammarus villosus invaded Britain from mainland Europe in 2010. Originating in the Ponto-Caspian region, this invader has caused significant degradation of European freshwater ecosystems by predating and competitively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…Among the ten microsporidians found in the present study, the D. duebenum- / D. muelleri- complex seems to be the most common in European amphipods. It was found in a variety of host species and shows the widest distribution among all amphipod-infecting microsporidians investigated [ 35 , 38 , 40 , 59 63 ]. This species complex was also most abundant in the present study and our data can add G. pulex clade C, E and G. fossarum type B as new hosts to this parasite group.…”
Section: Discussionmentioning
confidence: 99%
“…Among the ten microsporidians found in the present study, the D. duebenum- / D. muelleri- complex seems to be the most common in European amphipods. It was found in a variety of host species and shows the widest distribution among all amphipod-infecting microsporidians investigated [ 35 , 38 , 40 , 59 63 ]. This species complex was also most abundant in the present study and our data can add G. pulex clade C, E and G. fossarum type B as new hosts to this parasite group.…”
Section: Discussionmentioning
confidence: 99%
“…A mechanism explaining such patterns could be a purge of recessive deleterious alleles, which fuelled further population expansion, as evidenced in the ladybird Harmonia axyridis (Facon et al., ). Reduction in genetic diversity was also observed in populations of D. villosus after the colonisation of waterbodies in the U.K. (Arundell et al., ; Rewicz et al., ). Since the first initial population was discovered in 2010, the killer shrimp was detected in further four localities (Macneil et al., ).…”
Section: Discussionmentioning
confidence: 91%
“…Since the first initial population was discovered in 2010, the killer shrimp was detected in further four localities (Macneil et al., ). Its surprisingly slow spread in U.K. compared to the Alpine Lakes can be explained by the effective implementation of ‘check, clean and dry’ procedure (Arundell et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, histopathology (Bojko et al, 2013) and PCRbased (Arundell et al, 2015) studies of UK populations of the invasive amphipod Dikerogammarus villosus showed a distinct lack of pathogens and parasites when compared in invasive range across central (Etxabe et al, 2015) populations of D. villosus is suggestive of single-point introductions, rather than continual incursion events as previously observed throughout its continental invasive (Bojko et al, 2013). In contrast, Dikerogammarus haemobaphes, presents UK populations with high prevalence of parasites, such as the Microsporidia Dictyocoela berillonum and Cucumispora ornate (Bojko et al, 2015) or the Nematoda Hysterothylacium deardorffoverstreetorum (Etxabe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%